Village Service Information System - Sari, Sefrina Intan; Alfina (International Journal Education and Computer Studies (IJECS), 2021)
The purpose of this research is to design and build a Village Service Information System in order to improve the quality of services for village officials and the use of services for village residents. At the application development stage using the Scrum software development method and the application used is Microsoft visual foxpro 9. The results of the research that can be concluded are; 1) The ability and skills of village officials in communicating are still low so that in providing services to the community it does not provide satisfaction for the community, 2) Based on the database and form creation process using Microsoft Visual Foxpro 9.0, 3) Based on the database creation, the name of the database is db_pelayan, and the name the tables are tbl_kk, tbl_ktp, tbl_surat, 4) Based on the form using 7 forms, namely: Population Data Input Form, Family Input Form, Letter Administration Data Input Form, Search Form, Report Form, Login Form.